A newly isolated Pseudomonas otitidis phage, vB_PotS-PotUPM1 from tilapia in Malaysia - Tee, An Nie; Megat Mazhar Khair, Megat Hamzah; Chong, Chou Min; Mohd Shaufi, Mohd Asrore; Yusoff, Khatijah; Yam, Hok Chai; Gan, Han Ming; Song, Adelene Ai-Lian (Elsevier B.V., 2024)
A new Pseudomonas species, Pseudomonas otitidis was first known as an otic infectious agent in human. The presence of an inherent metallo-β-lactamase gene and its recent emergence in aquaculture underscore its potential zoonotic pathogenicity. The present study is aimed to characterize P. otitidis NK1 and its bacteriophage vBPotS-PotUPM1 (PotUPM1), which were isolated from an infected tilapia fish farm in Malaysia. P. otitidis NK1 showed beta-hemolysis on blood agar and is resistant to several antibiotics. Its genome size was 6067,534 bp, with an average nucleotide identity of less than 99 to all P. otitidis genome assemblies in GenBank, making it a novel strain of P. otitidis. The phage PotUPM1 has a latent period of 45 min and a burst size of 405 phage particles per bacterium. It effectively inhibited the growth of P. otitidis NK1 even at a low multiplicity of infection of 0.001 up to 9-hour post-inoculation. Transmission electron microscopy showed that it has a prolate head and a long, non-contractile tail, resembling those in the Siphoviridae family. Based on bioinformatic analysis, PotUPM1 has no resistance or virulence genes and is a lysogenic phage based on the presence of an integrase gene in the phage genome. Similarity analysis showed that PotUPM1 may represent a novel viral species with less than 95 nucleotide sequence similarity to other characterized phages. The findings of this study could provide an insight on the occurrence of P. otitidis in the aquaculture industry and lay a basis for the application of phage or phage-derived proteins against pathogenic P. otitidis to alleviate antimicrobial resistance.